Analysis trunk muscle activity and standing balance ability of archery athletes - Park, G.-E.; Han, T.-K. (Korean Journal of Sport Science, 2019)
The purpose of this study is to analyze the trunk muscles activity and standing balance ability according to the performance of archery athletes with excellent performance, and to utilize them as basic data for constructing a scientific training method. Participants were 11 selected athletes (SG) and 11 non selected athletes (NSG) in the national team second competition. The bow arm and draw arm side of the Erector Spinae muscle and Gluteus Medius muscle were analyzed byusing surface electromyography equipment. Standing balance such as symmetry, stability and sensorymotor of front/back and left/right was measured using MFT3Scheck. For comparisons between the groups, independent t - test was performed usingSPSS (version 22.0, Chicago, IL, USA). Following the results of trunk muscle activity analysis, elector spinae and guteus medius muscle activity of bow arm side in the NSG was significantly higher than the SG in the drawing phase. Based on the results of this study, it is suggested that the left/right balance ability is related to the performance in unilateral archery performance. Also, it is expected that these results can be used as basic data of archery performance improvement program including left/right stability training.